Eosinophilia and potential antibody cross-reactivity between parasites in a child with pinworm and immune dysregulation: a case report - Maria Di Cicco; Giulia Bertolucci; Carlotta Gerini; Fabrizio Bruschi; Diego G. Peroni (BMC, 2023)
Abstract Background Intestinal parasitic infections are common in humans, especially among young children. These conditions are often asymptomatic and self-limiting, and diagnosis is mainly based on the search for ova and parasites in the stools since serology may be biased due to cross reactivity between parasites. Pinworm is common in children and is not usually associated with hypereosinophilia; adhesive-tape test is the gold standard testing for the microscopic detection of Enterobious vermicularis (Ev) eggs. Case presentation A 13-year-old boy was referred due to a self-resolving episode of vomiting and palpebral oedema after dinner, together with a history of chronic rhinitis, chronic cough, absolute IgA deficiency and Hashimoto's thyroiditis and hypereosinophilia (higher value = 3140/µl). On evaluation we detected only palpable thyroid and hypertrophic nasal turbinates. Food allergy was excluded, but skin prick tests showed sensitization to house dust mites and cat epithelium and spirometry showed a marked obstructive pattern with positive bronchodilation test prompting the diagnosis of asthma for which maintenance inhaled treatment was started. Chest x-ray and abdomen ultrasound were negative. Further blood testing showed positive IgG anti-Echinococcus spp. and Strongyloides stercoralis and positive IgE for Ascaris, while Ev were detected both by the adhesive tape test and stool examination, so that we made a final diagnosis of pinworm infection. Three months after adequate treatment with pyrantel pamoate the adhesive-tape test turned out negative and blood testing showed a normal eosinophil count. The child later developed also type 1 diabetes. Conclusions We suggest the need to investigate for enterobiasis in children with hypereosinophilia and to consider autoimmunity as a potential confounding factor when interpreting serology for helminths.